2021
DOI: 10.2147/jir.s299010
|View full text |Cite
|
Sign up to set email alerts
|

Silenced SNHG1 Inhibited Epithelial-Mesenchymal Transition and Inflammatory Response of ARPE-19 Cells Induced by High Glucose

Abstract: The lncRNA small nucleolar RNA host gene 1 (SNHG1) is a cerebral infarctionassociated gene, its biological role and mechanism in diabetic retinopathy remain to be illuminated. The present study was designed to investigate the role of SNHG1 in high glucose induced human retinal pigment epithelial cells (ARPE-19). Methods: ARPE-19 cells were cultured and exposed to 60 mM high glucose for 48h, and 5.5mM glucose-exposed ARPE-19 cells were used as the control. The levels of the epithelial-mesenchymal transition (EM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…HG levels can promote the migration and proliferation of RPE cells, reducing the expression of epithelial markers E-cadherin and ZO-1 and increasing the levels of mesenchymal markers vimentin and α-SMA, indicating EMT ( Yang J. et al, 2021 ). A recent study showed that knockdown of miR-195 can inhibit EMT and RPE cell permeability ( Fu S. H. et al, 2021 ).…”
Section: Involved Cellsmentioning
confidence: 99%
“…HG levels can promote the migration and proliferation of RPE cells, reducing the expression of epithelial markers E-cadherin and ZO-1 and increasing the levels of mesenchymal markers vimentin and α-SMA, indicating EMT ( Yang J. et al, 2021 ). A recent study showed that knockdown of miR-195 can inhibit EMT and RPE cell permeability ( Fu S. H. et al, 2021 ).…”
Section: Involved Cellsmentioning
confidence: 99%
“…However, ARPE-19 cells are not immortal, heterogeneous and have an unrepresentative transcriptome ( Pfeffer and Fliesler, 2022 ). In present studies, ARPE-19 cells were used to observe epithelial-mesenchymal transition, oxidative stress, high glucose-induced injury and inflammation response ( Qian et al., 2019 ; Ravi et al., 2021 ; Yang et al., 2021 ; Yuan et al., 2020 ). Therefore, ARPE-19 cells were selected to evaluate the viral replication and subsequent inflammatory response in this research.…”
Section: Discussionmentioning
confidence: 99%
“…In the DR, the lncRNA small nucleolar RNA host gene 1 (SNHG1) is abnormally expressed (Yang et al, 2021). SNHG1 enhances vascular endothelial cell proliferation and angiogenesis in TNF-stimulated HUVEC (Zhang et al, 2020a).SNHG1-mediated histone changes are also implicated in neovascularization.…”
Section: Snhg1 and Snhg7mentioning
confidence: 99%